(3JaSjQ GdbQBfs - (3eMeO Hf Ydj Hf eMeO Hf YQHj , CHh HcQ GdMGJej GdWGFj GdCfOdSj, GdeYQha HeMjj GdOjf GHf YQHj,J (B638 (3g` s
(3ChdgG (B:s
(3de jcf GdPjf caQh CCi MLHhG eG Yf GdPi hWQjbI GdhUhd s
(3BNQgG (B:s
(3hceG CJjJ GdbOQ GdeTJQc ddeMLhHjf s
(3bWYI efgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B281s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA GdChd (B- ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B438s
(3eUOQ GbJfGA GdCUd (B:s
(3GdShOGfs
Keywords: (3GdJaSjQ hYdhe GdbQBfs